Strategi Penguatan Rantai Pasok Agribisnis untuk Menjaga Stabilitas Distribusi dan Harga Produk Pertanian - Albert Tunggul Ardiansyah; Dinni Ria Anggita; Oktaviane Situmorang; Rotua Julianti Simare Mare; Shella Anjelika Tampubolon; Yulan Hutabarat; Lokot Muda Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the agribusiness supply chain system and the factors that influence the efficiency of agricultural product distribution. The agribusiness sector has unique characteristics, such as seasonal products, perishable commodities, and a high dependence on natural conditions. These characteristics often create imbalances between supply and demand which lead to price fluctuations in the market. Through a literature review approach, this study examines various concepts and conditions of the agribusiness supply chain involving several actors, ranging from farmers, collectors, wholesalers, distributors, to retailers before the products reach the final consumers.The results of the study indicate that the efficiency of the agribusiness supply chain is strongly influenced by coordination among business actors, distribution systems, and the support of logistics infrastructure. Long distribution channels, limited transportation facilities, and inadequate storage facilities are some of the main obstacles that increase marketing costs and widen the price gap between producers and consumers. In addition, the perishable and seasonal nature of agricultural products requires faster and more integrated logistics management. Therefore, strengthening the supply chain system through infrastructure improvement, distribution integration, and the use of market information is an important step to improve distribution efficiency and maintain the stability of agricultural product availability in the market.